HİPERGEOMETRİK FONKSİYONLAR VE GAUSS DİFERENSİYEL DENKLEMİ İÇİN KESİRLİ ÇÖZÜMLER - KÜÇÜKER, NESLİHAN SABRİYE (Fırat Üniveristesi, 2015)
Bu tez beş bölümden oluşmaktadır. Birinci bölümde; kesirli hesaplamaların ve Gauss denkleminin tarihçesinden, bu konu ile ilgili ünlü matematikçilerin çalışmalarından bahsedilmiştir. İkinci bölümde; Hipergeometrik fonksiyon ve Gauss denkleminin kesirli çözümleri için kullanılan bazı tanımlar, fonksiyonlar ve teoremlerden bahsedilmiştir. Üçüncü bölümde; homojen Gauss denkleminin kesirli çözümlerinin bulunmasından bahsedilmiştir. Dördüncü bölümde; homojen olmayan Gauss denkleminin kesirli çözümlerinin bulunmasından bahsedilmiştir. Beşinci bölümde ise; homojen Gauss denkleminin kesirli çözümlerinin hipergeometrik fonksiyon biçiminde yazılışları elde edilmiştir.

This thesis consists of five chapters. In the first chapter; it is given the history of fractional calculus and Gauss equation, the works of famous mathematicians about this subject. In the second chapter; some definitions, functions and teorems used for fractional calculus for Hypergeometric Gauss equation are mentioned. In the third chapter; there has been mentioned of fractional solution of homogeneous Gauss equation. In the fourth chapter; it has been mentioned for fractional solution of non-homogeneous Gauss equation. In the fifth chapter; fractional calculus of homogeneous Gauss equation is obtained in the form of Hypergeometric function. Key words: Fractional Derivative and Integrals (Differintegrals), Gamma Function, Beta Function, Gauss Equation, Hypergeometric Functions, Leibniz's Rule.
Fractional calculus for Gauss equation and hipergeometric function
Keywords: Matematik